Make further vocational training pay. Possibilities and limits of promoting transitions by Public Employment Services (PES) - Konle-Seidl, Regina (Nürnberg, 2010)
"The current low participation rate of low-skilled workers in vocational re-training activities as well as the relatively high share of youth without vocational qualification are major challenges for German labour market policies. Recently implemented programs by the Federal Employment Service (BA) to improve the management of school-to-work transitions as well as re-training activities of already employed workers are analyzed in the framework of 'Transitional Labour Markets' (TLM). The TLM approach provides a series of proposals to manage social risks deriving from the need of making transitions during the life course. Preliminary evaluation results of early intervention and BA re-training programs are promising so far. However, extending the existing programs or even institutionalizing life-long learning as a social right by converting contribution based unemployment insurance into employment insurance - a prominent TLM recommendation - would require high financial resources and possibly undermine individual as well as corporate responsibility."